The British Empire c1857-1967 for AQA - Farmer, Alan (Access to history, 2018)
Exam Board: AQA Level: AS/A-level Subject: History First teaching: September 2015 First exams: Summer 2016 (AS), Summer 2017 (A-level) Give your students the best chance of success with this tried and tested series, combining in-depth analysis, engaging narrative and accessibility. Access to History is the most popular, trusted and wide-ranging series for A-level History students. This title: - Supports the content and assessment requirements of the 2015 A-level History specifications - Contains authoritative and engaging content - Includes thought-provoking key debates that examine the opposing views and approaches of historians - Provides exam-style questions and guidance for each relevant specification to help students understand how to apply what they have learnt This title is suitable for a variety of courses including: - AQA: 1J The British Empire, c1857-1967